Improving the Dynamics of Aid : Towards More Predictable Budget Support - Eifert, Benn; Gelb, Alan (World Bank, Washington, DC, 2012)
This paper considers approaches towards improving the predictability of aid to low income countries, with a special focus on budget support. In order to accelerate progress towards the Millennium Development Goals, the donor community is increasing aid flows while pushing for more coordination and tighter performance-based selectivity. However, these factors may increase the unpredictability of aid from current levels, which are already high enough to impose significant costs. Predictability is a particular challenge in the area of budget support, which will continue to increase in importance as aid is sought to underpin longer-term recurrent spending commitments. Budget support reduces transactions costs and drains on capacity, but it tends to be more vulnerable to fluctuations than multi-year project support. Poor predictability raises the threat of a low-level equilibrium: countries, budgeting prudently within a medium-term fiscal framework, will discount commitments; donors will see few funding gaps, so pledges will fall. With some countries discounting aid commitments in formulating budgets, some already see signs of this happening. To improve predictability, donors must extend their funding horizons. However, even if this can be done, several major issues will remain at country level. First, how can countries deal with residual short-run volatility of disbursements relative to commitments? Second, can donors lengthen commitment horizons to individual developing countries without excessive risk of misallocating aid? Third, within a country's overall aid envelope, how should donors set the shares of project aid and budget support? Finally, the paper considers the other main approach to budget support, the output or outcome-driven approach of the European Union. The paper concludes that many of these issues can be addressed. Simple spending and savings rules built around a buffer reserve fund of 2-4 months of imports can help smooth public spending. Aid can be pre-committed several years ahead with only small efficiency losses, using a strategy of "flexible pre-commitment." Guidelines can be set to limit the volatility of budget support while keeping it performance-based, and past experience can be used more systematically to develop "outcome" norms to better guide aid allocation.